2014
DOI: 10.1038/ijo.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for greater production of colonic short-chain fatty acids in overweight than lean humans

Abstract: BackgroundShort-chain fatty acids (SCFA) are produced by colonic microbiota from dietary carbohydrates and proteins that reach the colon. It has been suggested that SCFA may promote obesity via increased colonic energy availability. Recent studies suggest obese humans have higher faecal SCFA than lean, but it is unclear if this difference is due to increased SCFA production or reduced absorption.ObjectivesTo compare rectal SCFA absorption, dietary intake and faecal microbial profile in lean (LN) versus overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
197
4
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(220 citation statements)
references
References 54 publications
14
197
4
5
Order By: Relevance
“…There are ambiguous data about the effect of dietary fiber and SCFA on obesity development. While a systematic review published in 2011 [28] reports a slight but significant decrease of body weight (1.3%) with higher dietary fiber intake, recent literature data show a positive correlation between SCFA and obesity [9]. The positive effect of dietary fibers on obesity development is often correlated with a reduced appetite and thereby a decreased energy intake.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are ambiguous data about the effect of dietary fiber and SCFA on obesity development. While a systematic review published in 2011 [28] reports a slight but significant decrease of body weight (1.3%) with higher dietary fiber intake, recent literature data show a positive correlation between SCFA and obesity [9]. The positive effect of dietary fibers on obesity development is often correlated with a reduced appetite and thereby a decreased energy intake.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with this, several studies revealed that obese individuals have significantly higher fecal SCFA concentrations than lean individuals. Since this was not due to changes in the colonic absorption rate or dietary intake, it is taken as evidence for a higher production of SCFA in overweight individuals [9,10]. In apparent contrast to that, other results show a negative correlation between cecal SCFA production and obesity, and they suggest a protective effect of SCFA against dietinduced weight gain [11,12].…”
Section: Introductionmentioning
confidence: 90%
“…However, no consistent conclusions have been reached on changes of gut SCFA production in obesity. It has been demonstrated that fecal SCFA concentrations in rodent models of genetic obesity and overweight adult humans are higher than those of their lean counterparts, indicating an increased microbial energy harvest in obesity222327. However, in diet-induced obese mice fed a HFD with 45% calories from fat, reduced fecal SCFA (acetate and propionate) concentrations have been reported28.…”
Section: Discussionmentioning
confidence: 99%
“…Both animal and human studies indicate that cholesterol synthesis and other liver functions can be influenced by gut-derived SCFAs, even over short time scales [60], [61], [62], [63]. Bacteria producing SCFAs are less abundant in obesity and T2DM [6], but, strikingly, some studies found higher fecal SCFA concentrations in obese subjects [10], [64]. Evidence suggests that supplementation with these molecules may impact insulin sensitivity and energy expenditure in mice and humans [65], [66].…”
Section: Discussionmentioning
confidence: 99%